Cochlear Implant Remote Assist: Clinical and Real-World Evaluation. - Maruthurkkara, Saji (International Journal of Audiology, 2025)
Objectives: To develop and evaluate Cochlear™ Remote Assist (RA), a smartphone-based cochlear implant (CI) teleaudiology solution. The development phase aimed to identify the minimum features needed to remotely address most issues typically experienced by CI recipients. The clinical evaluation phase assessed ease of use, call clarity, system latency, and CI recipient feedback. Design: The development phase involved mixed methods research with experienced CI clinicians. The clinical evaluation phase involved a prospective single-site clinical study and real-world use across 16 clinics. Study sample: CI clinicians (N = 23), CI recipients in a clinical study (N = 15 adults) and real-world data (N = 57 CI recipients). Results: The minimum feature set required for remote programming in RA, combined with sending replacements by post, should enable the clinician to address 80% of the issues typically seen in CI follow-up sessions. Most recipients completed the RA primary tasks without prior training and gave positive ratings for usefulness, ease of use, effectiveness, reliability, and satisfaction on the Telehealth Usability Questionnaire. System latency was reported to be acceptable. Conclusion: RA is designed to help clinicians address a significant proportion of issues typically encountered by CI recipients. Clinical study and real-world evaluation confirm RA's ease of use, call quality, and responsiveness.